Temperament and Character traits in Bipolar “I” inpatients with and without substance abuse - Kheradmand, Azadeh; Semnani, Yousef (Open Science Journal, 2019)
Background: Bipolar disorder, a serious mental illness, affects a large number of people. They showed some differences in temperament and character traits in compared with healthy population. Moreover, they are prone to substance abuse. The aim of the study is comparing Temperament and Character traits in Bipolar “I” inpatients with and without substance abuse. Methods: In this Descriptive Cross-Sectional study, we recruited 228 patients with the diagnosis of bipolar I disorder by SCID-I. Patients’ temperament and character traits were assessed by Temperament and Character Inventory (TCI) questionnaire. Results: Novelty seeking showed significant differences between the groups with and without substance abuse or dependency. Logistic regression model showed that novelty-seeking score significantly correlated with substance abuse in-patient with bipolar disorder. Conclusion: Our findings indicated that novelty seeking is a major risk factor for substance abusing in bipolar patients